Effect of the Magnetic Field and Exhaust Gas Recirculation on the Performance and Emissions of Biodiesel Engine Coated with Nanoceramics - Qusai Mahdi; Mahmoud Mashkour; Ibtihal Mahmoud (Engineering and Technology Journal, 2024)
This study investigates the influence of ceramic coating on diesel engine efficiency through comprehensive analysis. The investigation was conducted on a four-stroke Kirloskar TV1 diesel engine. The study further examined the effects of employing an 8000 Gauss magnetic field and exhaust gas recirculation on engine performance. The surfaces of the head of the cylinder, the piston, and both the inlet and exhaust valves are then covered with nano-ceramic materials. Atmospheric plasma spray-created nanostructured thermal barrier coatings (TBCs). The feeding powder type is 7% Y2O3-ZrO2 with a particle size of less than 100 nm yttria stabilized zirconia (YSZ) nano X (S4007) ceramic surface coating (350 µm). Bond powder (NiCrAlY) Amdry 962, ranging from 56 to 106µm, has been utilized as a metal bonding coat (150 µm). The results show that the temperature of engine exhaust rises after coating, resulting in a decrease in fuel consumption by 14.22 %. The effect of biofuels on the performance of a compression ignition engine running on diesel fuel was examined. The testing findings revealed that brake thermal efficiency (BTE) improved by 20.5%, and brake-specific fuel consumption (BSFC) decreased by 18.1%. When the load goes up from 50 to 100 percent, however, 38.8 percent and fewer CO percent are observed for the B10+10EGR+8000 Gauss and 0.5 mm coated engine. Also, acceptable increases in emissions were observed in CO2 levels. Diesel and the B10+EGR10+8000 Gauss un-treatment engine's NOx emission values rise by 49.15 percent and 45 percent, respectively, after the load goes up 75 percent.